Hair diseases: a big problem on a small surface - Brzezińska-Wcisło, Ligia A.; Wcisło-Dziadecka, Dominika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Civilizational progress initially contributes to the problem of hair loss and then to alopecia as regards both frequency and therapeutic dilemmas. The work presents trichological problems which occur more rarely, i.e. drug-induced, anagen and telogen alopecia, congenital and acquired structural hair disorders, psychic disturbances concerning the hair as well as the hair during menopause. Then, the article briefly describes contagious (infectious) diseases as well as diseases with inflammatory etiology which are accompanied by exfoliation and (frequently) pruritus. Finally, alopecia cicatricans is discussed. Alopecia areata and androgenetic alopecia are omitted herein because they occur more often and will be described in another work. Any disproportions and upset balance concerning correct functioning of mechanisms within the scalp hair system are the evidence of pathologies.